PENGARUH ALKALI SILIKA REAKTIF PASIR TERHADAP KUAT TEKAN MORTAR RENDAMAN - Mudiono Kasmuri; Ajeng Ayuningtias (Politeknik Negeri Jakarta, 2023)
Mortar is a building material made of cement, fine aggregate, and water. To get a good mortar strength, the properties, and characteristics of each of the mortar constituents must also be studied further. Aggregates containing silica can be reactive or non-reactive to alkaline elements in cement. The purpose of this study was to determine the effect of alkaline silica reactive sand on the compressive strength and flexural strength of mortar immersed in seawater. This research uses an experimental method, namely Rangkas sand, Bangka sand and Lumajang sand which have gone through the XRF (X-Ray Fluorescence) testing process to determine the percentage of compound content contained. The research method to determine the reactivity of the sand refers to ASTM C 1260. The compressive strength and flexural strength of the mortar were tested with two variations of immersion, namely by using fresh water and sea water. The immersion of the mortar was carried out for 7, 14, 28 and 56 days. From the results of testing the compressive strength and flexural strength of mortar at the age of 28 days had the same results for fresh water and seawater immersion, namely sand with high potential for reactive alkali silica has low compressive strength and flexural strength values ​​for all types of immersion. The freshwater immersion method has been used to test the mortar's flexural and compressive strength. It has a higher compressive and flexural strength value than the seawater immersion mortar, with a percentage ratio of 27.1% of compressive strength and 17.3% of flexural strength in mortar, with an immerse age of 28 days.